2003
DOI: 10.1093/toxsci/kfg218
|View full text |Cite
|
Sign up to set email alerts
|

Region-Specific Inhibition of Prostatic Epithelial Bud Formation in the Urogenital Sinus of C57BL/6 Mice Exposed in Utero to 2,3,7,8-Tetrachlorodibenzo-p-dioxin

Abstract: In utero 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) exposure causes abnormal ventral, dorsolateral, and anterior prostate development in wild-type but not aryl hydrocarbon receptor (AhR) null mutant C57BL/6 mice. Experiments have now been conducted to test the hypothesis that TCDD causes an AhR-dependent inhibition of the earliest visible stage of prostate development, the formation of prostatic buds by urogenital sinus (UGS) epithelium. A novel method for viewing budding was developed that uses scanning elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
100
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(101 citation statements)
references
References 23 publications
1
100
0
Order By: Relevance
“…Since transgenic loss of Hoxd13 has been shown to decrease the number of dorsolateral buds (Podlasek et al, 1997), it seems quite plausible that RA-induced changes in Hox gene expression and UGS patterning could result in additional or expanded domains of budding and supernumerary bud formation. Lin et al (2003) demonstrated the C67BL/6J male mouse UGS reproducibly displays 8 ventral buds, an average of 52 dorsolateral buds and 5-6 anterior buds on E18.5, but since the three-dimensional UGS shape is distorted during incubation in UGS organ culture, the regional identity of buds cannot be reliably determined. Therefore, it was not possible to determine from the present study whether the induction of supernumerary prostatic buds by RA was restricted to specific lobes, interlobular boundary regions, or a generalized effect on the UGS as a whole.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since transgenic loss of Hoxd13 has been shown to decrease the number of dorsolateral buds (Podlasek et al, 1997), it seems quite plausible that RA-induced changes in Hox gene expression and UGS patterning could result in additional or expanded domains of budding and supernumerary bud formation. Lin et al (2003) demonstrated the C67BL/6J male mouse UGS reproducibly displays 8 ventral buds, an average of 52 dorsolateral buds and 5-6 anterior buds on E18.5, but since the three-dimensional UGS shape is distorted during incubation in UGS organ culture, the regional identity of buds cannot be reliably determined. Therefore, it was not possible to determine from the present study whether the induction of supernumerary prostatic buds by RA was restricted to specific lobes, interlobular boundary regions, or a generalized effect on the UGS as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…UGS epithelium was then fixed in 2.5% glutaraldehyde and evaluated by scanning electron microscopy (SEM). SEM was performed as previously described (Lin et al, 2003). UGS specimens were imaged from 4 angles to visualize budding across the entire UGS surface.…”
Section: Ugs Organ Culture and Bud Countingmentioning
confidence: 99%
See 3 more Smart Citations